Adsorption of Cr(VI) on Agricultural Byproducts - Farroqui, Mazahar; Kotharkar, Sandeep (Asian Journal of Chemistry, 2010)
The methi stem due to its well known adsorption characteristics has been taken for removal of Cr(VI) from the effluent. The result shows an encouraging high percentage removal of Cr(VI). Spectrophotometric method has been utilized with diphenyl carbazide as a reagent.